PENDAMPINGAN PEMBENTUKAN BADAN USAHA MILIK DESA (BUMDES) DESA KENDALASEM WEDUNG DEMAK - Amrina Rosyada (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
This engagement partner is the goverment of Kendalasem village , Wedung, Demak. The main problem of partners is the unbalanced abundance of potential possessed by the lack of human resources and ignorance about village’s business institution (Bumdes). Therefore, the engagement team made a program, namely the Formation of Bumdes for Kendalasem village. The methods used are education, outreach, training and assistance. The results of this dedication are: a) the formation of the Bumdes officially named Kendalasem Jaya; b) The village’s potentials had been mapped; c) the bumdes management team and business units had been formed ; and d) the village regulation related to Bumdes had been made. This community engagement program has a significant impact in establishing Bumdes as a step to increase community participation in order toimprove the economy and welfare of the community.